(3ebGHS GdCfhGQ hfaGFS GdCSQGQ aj CMcGe GdfHj GdeNJGQ hYJQJg GdCWgGQs - (3GdcGXej, GdORahdj, CSO Gddg Hf ESeGYjd, J (B1220(3g`s
(3ChdgG (B:s
(3fMeOc jG ef CHdL HebGHS CfhGQ gOGjJg TQGFY GdESdGe(B... (3hHYO ajbhd(B... (3CSO Gddg(B... (3gPG eG GTJOJ Edjg GdCThGb(B... (3ef JMQjQ cJGH aGFb aj HjGf CegGJ GdCMcGe GdTQYjI(B...s
(3BNQgG (B:s
(3hcGf Mce GdeQCI aj GdEQK Mce cd eWdbI KHJ WdGbgG HGdHjfI(B... (3ajcf gPG BNQ eHdZ GdfXQ hfJjLI GdacQ(B...s
(3JHUQI GdeDda (B:s
(3haGJg aj gOjI GdYGQajf(B: 1220(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI HQbe(B: 5535s
(3gOjI GdYGQajf(B: (3L(B1(3, U(B203s
(3GdPQjYI HQbe(B: 5535s
Keywords: (3abg GdePGgH GdCNQis